Pengaruh Bahan Organik dan Azotobacter terhadap pertumbuhan Jagung di Tailing terkontaminasi merkuri dari Pulau Buru - Reginawanti Hindersah; A. Marthin Kalay; Rafael Osok (Agrologia, 2018)
Characteristics of mineral-mine tailings deposited in agricultural areas do not meet the requirements for food crop cultivation. The objective of the experiment was to obtain the information on the improvement of plant growth planted in mercury-contaminated tailings after adding organic matter and nitrogen fixing bacteria, Azotobacter. The greenhouse trial was set up in randomized factorial design which tested the Azotobacter inoculation consentrations and organic matter doses. There was no interaction effect between the two treatments on the growth of four-week old corn. Both organic matter and Azotobacter had a positive impact on vegetative growth of corn.